On Uighur Wedding Traditions and Change (Uygur Düğün Gelenekleri ve Değişimi Üzerine) - Mairihaba Wufuer (Skad)
As a former nation, there is a long history of Uighur and a long tradition of customs. The search for material life with the development of society is very evident in marriage. Many rituals are simplified in Uighur weddings and marriage traditions are more influenced by directions. The ceremony is one of the most important factors in marriage. Wedding ceremony is not only the social system, but also the religious factors, economic conditions, regional traditions, ethics and the absorption of foreign cultures are related factors.In the article, the removal and change of some traditions in the marriage path and wedding ceremonies of the Uighurs.